Model Pembelajaran Jigsaw Dalam Meningkatkan Kemampuan Bahasa Inggris I Mahasiswa PPKn FIS UNESA - Arik Susanti, ; Anis Trisusana, (Widya Cendika, 2011)
Teaching English is not easy especially for non-English department. It is required a method to motivate the students in order to study English well. In the classroom action research is used kooperatif learning Jigsaw type to improve the students score and to motivate them. The results show that this method is very effective to develop the students capability. Most of them like to study English.